2013
DOI: 10.3892/ijmm.2013.1391
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effect of N-acetyl-L-cysteine against acute cocaine toxicity in rat C6 astroglial cells

Abstract: Astroglial cells are one of the most abundant cell types in the mammalian brain functioning in neuronal survival and in maintenance of fundamental patterns of circuitry. To date, no study has been conducted regarding the short-term impact of cocaine on these cells in cultures. The present study aimed to investigate acute cocaine (1 h) treatment on cell viability in rat C6 astroglial cells. In addition, the potential effect of N-acetyl-L-cysteine (NAC) against cocaine-induced toxicity was studied. It was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
5
7
0
Order By: Relevance
“…3C ). Similar observations were recently reported for NAC pretreatment ( 13 ). In addition, we showed that the increased cell viability of cocaine-treated cells is accompanied by an increase in the GSH level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…3C ). Similar observations were recently reported for NAC pretreatment ( 13 ). In addition, we showed that the increased cell viability of cocaine-treated cells is accompanied by an increase in the GSH level.…”
Section: Discussionsupporting
confidence: 92%
“…Under our experimental conditions, the cocaine LC 50 in C6 astroglial cells was ~3 mM at 1 h exposure. This value is closer to that of a recent report ( 13 ). It is notable that cocaine was not prominently toxic to liver and kidney cells or to living shrimp larvae ( Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Following uptake of cystine into cells via system xc‐, cystine can be converted back into cysteine to allow for the synthesis of further glutathione. This has been shown in an experiment where incubation of cultured astroglial cells with a cocaine/NAC mixture prevented the cocaine‐induced decrease in cell viability by increasing cellular glutathione levels (Badisa et al ., , ). Furthermore, NAC may also increase the expression of antioxidant enzymes, with a cell culture model of cocaine‐induced hepatotoxicity finding increased manganese‐ and copper, zinc‐superoxide dismutase, catalase and glutathione peroxidase levels following NAC supplementation (Zaragoza et al ., ).…”
Section: Potential Therapies For Addiction May Influence Redox Statusmentioning
confidence: 99%
“…185 In keeping with this, NAC was found to reverse GSH depletion in rat astroglial cells following cocaine-induced oxidative stress. 186,187 Regrettably, clinical trials of NAC efficacy as a treatment for substance use disorders have received mixed results. 188 However, these results do suggest that drugs affecting glutathionylation are valid areas of research in addiction pharmacotherapy.…”
Section: Future Researchmentioning
confidence: 99%